Charge Carrier Mobility Analysis of Chlorophyll Thin Film Spirulina sp Produced by Spin Coating - Muhamad Mustain; Defi Sulistyana; Utari U; Budi Purnama (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Analysis of carrier charge mobility of Spirulina sp thin films produced by spin coating havebeen conducted. Measurement of carrier charge mobility has been done by I-V method.Mobility of carrier charge decreased with an increased of the layer number. It indicates that athreshold value of carrier charge of population number over flow on conduction band.